2004
DOI: 10.1158/0008-5472.can-03-2100
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Mutations and Altered Expression of the Candidate Tumor Suppressors CSNK1ε , DLG1 , and EDD/hHYD in Mammary Ductal Carcinoma

Abstract: We report somatic mutations in three genes (CSNK1⑀, encoding the Ser/Thr kinase casein kinase I ⑀; DLG1, encoding a membrane-associated putative scaffolding protein; and EDD/hHYD, encoding a progestin induced putative ubiquitin-protein ligase) in mammary ductal carcinoma. These genes were suspected of playing a role in cancer because loss-offunction mutations in their Drosophila homologues cause excess tissue growth. Using DNA from 82 laser-microdissected tumor samples, followed by microsatellite analysis, den… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
111
2
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(123 citation statements)
references
References 55 publications
8
111
2
2
Order By: Relevance
“…Although somatic mutations in the EDD gene have been reported in gastric and colorectal tumours (Mori et al, 2002) and in mammary ductal carcinoma (Fuja et al, 2004), we have not identified any deleterious EDD mutations in a number of ovarian cancer cell lines (Clancy et al, 2003), and therefore, we predict that EDD mutation would be a very rare event in ovarian cancer and hence assume that EDD is functional in ovarian cancer.…”
Section: Discussioncontrasting
confidence: 59%
“…Although somatic mutations in the EDD gene have been reported in gastric and colorectal tumours (Mori et al, 2002) and in mammary ductal carcinoma (Fuja et al, 2004), we have not identified any deleterious EDD mutations in a number of ovarian cancer cell lines (Clancy et al, 2003), and therefore, we predict that EDD mutation would be a very rare event in ovarian cancer and hence assume that EDD is functional in ovarian cancer.…”
Section: Discussioncontrasting
confidence: 59%
“…Several reports have also demonstrated that EDD1 is overexpressed in a high percentage of cancers, consistent with a pattern that correlates with an increased copy number of the EDD1 locus (27,28). Finally, cancer-specific somatic mutations of EDD1 have been observed; however, the functional consequence of the mutations are unknown (28,29). As with EDD1, several studies have reported cancer-specific aberrations of GRHL2.…”
Section: Discussionmentioning
confidence: 67%
“…Evidence to date has been suggestive but indirect. Large-scale sequencing of nTSG homologs from mammalian tumors has not yet been performed, but a small-scale study has reported Dlg1 mutations in breast cancers (Fuja et al 2004), and microarray experiments have detected significant changes of nTSG homolog expression in several human cancers (Liu et al 2002;Boussioutas et al 2003). Immunohistochemistry has revealed a reduction of hScrib in invasive cervical cancers and Dlg1 in mammary ductal carcinoma, as well as reduction of Dlg4 in a fully defined model of mouse ovarian cancer (Huang et al 2003;Nakagawa et al 2004).…”
Section: Do Vertebrate Ntsg Homologs Play a Role In Cancer?mentioning
confidence: 99%
“…Drosophila has come into its own in particular as a system in which to identify new TSGs, and the relevance of fly TSGs to human cancer has become increasingly clear. The past few years have seen reports that TSGs first identified in the fly are mutated in human cancers and can cause tumor susceptibility in mice (e.g., St John et al 1999;Spruck et al 2002;Fuja et al 2004;Rajagopalan et al 2004). Analyses of fly TSGs have also produced substantial contributions toward understanding the basic cell biology of tumorigenesis, in particular links between cell growth, cell proliferation, and apoptosis.…”
mentioning
confidence: 99%